Front Cover Picture: Palladium‐Catalyzed Regioselective C−H Arylation of 4‐Azaindazole at C3, C5 and C7 Positions (Adv. Synth. Catal. 16/2021). Issue 16 (26th July 2021) - Faarasse, Soukaina; El Kazzouli, Saïd; Bourzikat, Otmane; Bourg, Stéphane; Aci‐Sèche, Samia; Bonnet, Pascal; Suzenet, Franck; Guillaumet, Gérald
Abstract : The front cover picture, designed by El Kazzouli and co‐workers, illustrates the site‐selective C5 and C7 palladium‐catalyzed C‐H arylations of 4‐azaindazole N ‐oxide. The 1, 10‐phenanthroline as ligand and Pd(OAc)2 as catalyst in toluene promoted the activation of C5 position, while the triphenyl phosphine as ligand and PdCl2 as catalyst in DMA directed the arylation at C7 position. This new method allows the synthesis of C5, C7‐diarylated 4‐azaindazole N ‐oxides as well as the C3, C5, C7‐triarylated 4‐azaindazoles. Details can be found in the Communication by El Kazzouli, Suzenet, Guillaumet and co‐workers (S. Faarasse, S. El Kazzouli, O. Bourzikat, S. Bourg, S. Aci‐Sèche, P. Bonnet, F. Suzenet, G. Guillaumet Adv. Synth. Catal . 2021, 363, 3937–3945; DOI: 10.1002/adsc.202001421 ).